DFT Study of the Stability, Electronic, Optical, and Thermal Properties of Two-Dimensional BiBr₃ Semiconductor - Shwan, Yadgar Hussein; Ameen, Majida Ali; Mahmood, Aras Saeed (East European Journal of Physics, 2026)
Density functional theory (DFT) serves as a first-principles method to thoroughly investigate the stability of the structure and analyse the electronic, optical, and thermal characteristics of two-dimensional bismuth tribromide (2D BiBr3). Ab-initio molecular dynamic (AIMD) simulations reveal that the structure is thermally stable at 300 K. The BiBr3 behaves as a semiconductor with a 2.84 eV band gap according to its electronic band structure and partial density of state (PDOS) analysis. Optical characterisation reveals that BiBr3 has strong interactions in visible and ultraviolet wavelength domains, which shows its potential in the next-generation of optical and optoelectronic devices. A remarkable Seebeck value estimated via Boltzmann transport calculations, highlights the promise of BiBr3 in low-temperature thermoelectric management. This investigation implies temperature-driven power factor improvement, peaking at 3.25 ×1012 W/K2·cm·s at 300K. The BiBr3 exhibits moderate heat capacity at intermediate to high temperatures while keeping verylow thermal conductivity. This highlights its ability to effectively manage heat and serve as an insulator in various applications. The detailed results show that 2D BiBr3 is a potentially favorable material with diverse possibilities in most technological applications.